Pembelajaran Sejarah Melalui Latihan Soal Pilihan Ganda Untuk SMA Di Kota Lubuklinggau - Ratna Wulan Sari; Agus Susilo (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
History opens a window to the past to welcome the future, learning history will help to know and understand how the history of the past and also the people associated with these events. Studying history not only aims to know important events or events in the past but also teaches various forms of experience that occur both success and failure. Every human being needs education and knowledge because it is for human development itself. Through education, humans not only get teaching about special skills but also something deeper, namely science. In the world of education through learning, students gain knowledge and learn what is obtained through learning. Each student will pass the evaluation stage. The evaluation is given after students have gone through several learning and understanding processes and then given questions, both essays and multiple choice questions, in order to help the learning process in the classroom. To maximize the use of multiple choice as a learning tool, students can choose it with consideration in the answer choices that have been determined. Teachers give assignments to students to work on multiple choice questions in two ways, the first is to solve multiple choice questions, when given an assignment during class hours to submit it to the teacher when the subject is finished. Alternatively, the teacher can give the students an assignment or homework and collect it during the next meeting. Research shows that teachers prefer the use of multiple choice questions, not only because of administration, time saving and simplicity but also because they are objective and consistent. Furthermore, students based on the results of the study prefer giving multiple choice questions because they can eliminate answer errors and the questions on multiple choice questions are more objective than others. In addition, with the multiple choice question method students can actively participate in the learning process.